A design methodology for user access control (UAC) middleware - Steele, R.; Gardner, W.; Rajugan, Rajagopal; Dillon, Tharam S. (IEEE, 2005)
XML repositories are increasingly becoming popular to store data or as an interoperability layer for legacy applications and data sources. The widespread use of XML highlights the need for flexible and expressive access control models for XML documents to protect sensitive and valuable information from unauthorised access. Metadata for advanced context representation is likely to play an increasingly important role within access control models and languages for active Web data. Importantly, access control for both human users and machine users must be supported. This paper presents an XML views-based access control model, which supports access control for both human and machine data users. The design methodology we propose here is based on XML views and supports 'conceptual level' design of UAC constraints.